ChemInform Abstract: Copper‐Catalyzed Aerobic Oxidative Annulation and Carbon—Carbon Bond Cleavage of Arylacetamides: Domino Synthesis of Fused Quinazolinones. Issue 33 (19th August 2014) - Sun, Jie; Tan, Qitao; Yang, Wusong; Liu, Bingxin; Xu, Bin
Abstract Cu‐catalyzed tandem reactions of phenylacetic acid amides having a 2‐pyridyl or related heteroaryl substituent proceed through aerobic benzylic oxidation, intermolecular cyclization, and decarbonylation to yield a variety of fused quinazolines.